The Effect of Current Ratio, Debt to Equity Ratio and Return on Equity Ratio on Stock Prices - Ar, Mursalim; Matyani, Matyani; Sofyaun, Ashari (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to determine the influence of Current Ratio, Debt to Equity Ratio, Return on Equity on Stock Prices. The study was conducted on Automotive Component Subsector Companies listed on the Indonesia Stock Exchange for the period 2019-2024. Sample selection was carried out using the purposive sampling technique and 9 companies were obtained, with a total of 54 observation data. The findings of the study showed that the Current Ratio had no effect, while the Debt To Equity Ratio and Return On Equity Ratio partially succeeded in having a positive effect on stock prices.